The Relationship between Stigma, Resilience, and Quality of Life from Family Members Taking Care of Schizophrenic Patients - Nihayati, Hanik Endang; Herawati, Ira; Wahyudi, Andri Setiya (International Journal of Psychosocial Rehabilitation, 2020)
Stigma in society about people with mental disorders, especially for schizophrenic patients, is very high. Stigma is not only given to schizophrenic patients but also their family members. The stigma given to family members may cause them to feel sad, ashamed, shocked, annoyed, uneasy, and blaming one another. This can affect the resilience and quality of life from family members who are taking care of schizophrenic patients. This study applied cross-sectional research in which the population was family members who accompany the schizophrenia patient to psychiatric polyclinics. The total of samples was 171 respondents who met several criteria, namely family members who were taking care of and living in the same house with the schizophrenic patients; cooperative; and be able to read and write. The variables of this study were stigma, resilience, and quality of life. Data collection was conducted using a questionnaire and analyzed using the Spearman’s rho test. It showed that there were a very strong negative relationship between stigma and resilience (p = 0.000 and r = -0,851) and between stigma and quality of life (p = 0,000 and r = -0,715). Efforts to reduce stigma in society regarding schizophrenia must be carried out because stigma affects not only schizophrenic patients but also the family members who are taking care of them. The high resilience and good quality of life have positive effects on the healing process and reduce the relapse rate of schizophrenic patients.